PAKISTAN'S SECURITY RELATIONS WITH KENYA, SOUTH AFRICA AND NIGERIA: A COMPARATIVE ANALYSIS (Margalla Papers, 2023)
This study examines Pakistan's security relations with Kenya, South Africa and Nigeria, specifically focusing on the influence of geopolitical, economic and cultural factors. Three main research questions guide the research: a) what are the similarities and differences in Pakistan's security relations with these three countries? b) How do geopolitical factors shape Pakistan's security relations with each country? c) What roles do cultural and economic ties play in shaping these security relationships? The study identifies and compares similarities and differences in security relations among these countries, highlighting the unique historical, geopolitical, and cultural factors through a multidimensional approach, drawing insights from Realism, Constructivism and Neoliberal Institutionalism. The findings underscore the significance of considering power dynamics and cultural influences in understanding security relations. Furthermore, the study sheds light on the potential of international institutions in promoting cooperation and building trust between Pakistan and its African counterparts. Bibliography EntryKhan, Tariq. 2023. "Pakistan's Security Relations with Kenya, South Africa and Nigeria: A Comparative Analysis." Margalla Papers 27 (1): 123-137.